Review of Ethnic Identities in the Land of the Pharaohs - de Souza, Aaron M..
Uroš Matić, Ethnic Identities in the Land of the Pharaohs. Cambridge: Cambridge University Press, 2020. Elements in Ancient Egypt in Context 2. ISBN 978-1108885577. 82 pp. with B&W and colour images.